Mineralogy, petrochemistry and genesis of scheelite-bearing skarns and related acid magmatism at Sargipali, Eastern India - Chowdhury, S (Journal of Nepal Geological Society, 2008)
In Sargipali of Eastern India scheelite-bearing calc-silicate skarn rocks are reported in the so-called Gangpur Group, a metasedimentary geologic unit now in greenschist to amphibolite facies. The skarn rocks, both calcic exoskarn (garnet-pyroxene) and endoskarn (pyroxene-epidote) occur at the contacts of dolomites and granitoids in close association with the mica schist hosted Proterozoic Pb-Cu- Ag sulfide deposits. The skarn rock itself is barren of sulfide mineralization. The main constituents of the scheelite-bearing rocks are clino-pyroxene, garnet, calcic amphiboles (K-rich ferropargasite and hastingsite, ferrohornblende, magnesiohornblende, tschermakite and actinolite), wollastonite, plagioclase, potash feldspar, epidote, sphene, quartz and magnetite. The granitic complex corresponds to reduced, highly evolved and metallogenically specialized Stype leucogranites, comparable to those commonly associated with Mo-poor W-F skarns. Three distinct and two poorly developed calc-silicate zones are observed between dolomite and granitic intrusive at Sargipali. The zones are characterized by pyroxeneclinozoisite, garnet, epidote and amphibole-plagioclase. The observed zonal sequence is close to that predicted by a simple model of cation diffusion metasomatism The calc-silicate skarns are notably enriched in Al, Mg and Fe, and garnets are grossularite-almandine with 1 to 10 mole percent spessartine while pyroxenes are hedenbergitic to diopssidic in composition. Average Fe/Mn ratio (and mole percent hedenbergite) in pyroxene decreases with distance from garnet zones and correlates with an increase in Mg, suggesting a progressive depletion of Fe in solution due to precipitation of Fe-rich garnet, and a progressive enrichment in Mg in the fluid as it approached equilibrium with dolomitic wall rocks. The skarns formed initially at about 5000- 7000 C and of 5-6 kbar pressure in a mildly reducing environment during the amphibolite-facies regional metamorphism and were altered subsequently at lower temperatures (< 5000 C). The paper documented herein comprises a detailed study of the deposit geology, providing the basis for calc-silicate mineral chemistry and geochemical investigations of skarn and granitoids. This paper also summarises the salient features of the Sargipali granitoid to compare with other worldclass tin-tungsten skarns. This comparison suggests a direct relationship between magmatic fluid and Sn-W mineralisation, and the similarity of the geochemical characteristics of the Sargipali granitoids to averages for W- and Sn- skarn granitoids. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.8